(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Effect of oral administration of “Gadagi” tea on some hormones was assessed on healthy male albino rats which were grouped and administered with different doses i.e low dose, standard dose and high dose of “sak’’,”sada” and “magani” respectively for a period of four weeks. Animals that were not administered with the tea constituted the control group. At the end of fourth week, the animals were sacrificed and their serum adrenaline, insulin, adrenacorticotrophic hormone (ACTH) and glucagon were determined. Mean serum ACTH level was found to be significantly lower (P<0.05) at low dose level of “sak”, standard and high dose levels of “sada” and at low dose of “magani” than that of the control group. Mean serum insulin level of rats administered with “sada” at low dose level was found to be significantly lower (P<0.05) than that of the control rats. Mean serum glucagon level was found to be significantly higher (P<0.05) in standard dose group of “sak”, low and standard dose groups of “sada” and “magani” than that of the control group. This indicates an increase level of conversion of glycogen into glucose for energy generation. Therefore, from the results of the study, the increase in the power of endurance experienced by the “Gadagi” tea users could be associated with an increase in glucagon level and probable decrease in insulin level